An efficient ray tracing propagation simulator for analyzing ultrawideband channels - Tiberi, G; Bertini, S; Malik, W; Monorchio, A; Edwards, D; Manara, G (2007)
A fundamental step in ultrawideband (UWB) communication systems involves the characterization of the indoor propagation channel. In this paper, we show that UWB channel parameters can be predicted accurately by ray tracing (RT) simulation carried out at various frequencies over the signal bandwidth. Our RT algorithm is independent of frequency, therefore the determination of the rays reaching a given location is made only once. Moreover, a parallel ray approximation is used to improve significantly the computational efficiency of the RT based approach. The excellent agreement between simulation results and measured data proves that our RT-based tool can be used successfully for accurate and reliable site-planning in UWB systems. © 2007 IEEE.